Hubungan antara Motivasi Belajar dan Kesiapan Karir Siswa SMK Negeri 01 Karanganyar - Annisa Indah Damayanti; Salma Belva Calysta (Lembaga Yasin AlSys, 2026)
Although the issue of low career readiness among vocational high school graduates has been widely discussed, research that specifically highlights the role of learning motivation as an internal factor influencing students’ career readiness remains limited, particularly in the context of regional vocational schools. This study aims to analyze the relationship between learning motivation and career readiness among students at SMK Negeri 01 Karanganyar. A quantitative approach with a correlational design was employed, involving 169 Grade XII students selected using a saturated sampling technique. Data were collected using four-point Likert scale questionnaires whose validity was tested with Corrected Item–Total Correlation and reliability with Cronbach’s Alpha. Data analysis was conducted using descriptive statistics, the Kolmogorov–Smirnov normality test, and Pearson Product–Moment correlation. The results show that all items for both variables are valid (r > 0.152) and reliable (α = 0.812 for learning motivation and α = 0.681 for career readiness), the data are normally distributed (p = 0.200), and there is a positive and significant relationship between learning motivation and students’ career readiness (p < 0.05). These findings contribute to the development of motivation theory and career development theory, particularly in explaining the role of students’ internal factors in their readiness to enter the world of work. The study concludes that learning motivation is an important factor that needs to be strengthened through instructional strategies and career guidance programs in vocational schools, with theoretical implications for enriching the literature on motivation and career readiness, and practical implications for schools in designing interventions to enhance students’ career readiness and opening avenues for further studies on other variables that may influence career readiness.